Early numerical skills and mathematical domains in autistic students in primary school - Bejarano-Martín, Álvaro; Casado-Vara, Roberto; Magán-Maganto, María; Díez, Emiliano; Jenaro, Cristina; Flores, Noelia; Orrantia, Josetxu; Canal-Bedia, Ricardo (Frontiers in Psychiatry, 2024)
IntroductionIt is crucial to provide a quality educational response to the needs of autistic children across various mathematical domains. However, there is no consensus on which of the early skills have the greatest predictive effect in the short and long term within these domains. Therefore, this research aimed to a) compare early numerical skills and mathematics domains, and 2) analyze the predictive value of early numerical skills into mathematics domains.MethodsForty-two children (twenty-one autistic children and twenty-one non-autistic children) aged 6-12 years participated in the study. Three areas were evaluated through different tasks: 1) control tasks: reading, impulse control and manual speed, 2) early numerical skills: counting, verbal subitizing, magnitude comparison and estimation, and 3) mathematical domains: arithmetic calculation and arithmetic word problems.ResultsSignificant differences were found in subitizing and estimation tasks. Both groups showed similar mathematical skills in arithmetic calculation and arithmetic word problems. For autistic students, several non-symbolic tasks predict performance in mathematical domains, whereas for non-autistic students, symbolic tasks were predictors.DiscussionAlthough mathematics does not seem to be an area of concern for autistic children, future studies should explore early numerical and mathematical domains in children with cognitive support needs through longitudinal research.